Emerging role of non‐coding RNA in health and disease - Bhatti, Gurjit Kaur; Khullar, Naina; Sidhu, Inderpal Singh; Navik, Uma Shanker; Reddy, Arubala P.; Reddy, P. Hemachandra; Bhatti, Jasvinder Singh (Metabolic brain disease, 2021)
Human diseases have always been a significant turf of concern since the origin of mankind. It is cardinal to know the cause, treatment, and cure for every disease condition. With the advent and advancement in technology, the molecular arena at the microscopic level to study the mechanism, progression, and therapy is more rational and authentic pave than a macroscopic approach. Non-coding RNAs (ncRNAs) have now emerged as indispensable players in the diagnosis, development, and therapeutics of every abnormality concerning physiology, pathology, genetics, epigenetics, oncology, and developmental diseases. This is a comprehensive attempt to collate all the existing and proven strategies, techniques, mechanisms of genetic disorders including Silver Russell Syndrome, Fascio- scapula humeral muscular dystrophy, cardiovascular diseases (atherosclerosis, cardiac fibrosis, hypertension, etc.), neurodegenerative diseases (Spino-cerebral ataxia type 7, Spino-cerebral ataxia type 8, Spinal muscular atrophy, Opitz-Kaveggia syndrome, etc.) cancers (cervix, breast, lung cancer, etc.), and infectious diseases (viral) studied so far. This article encompasses discovery, biogenesis, classification, and evolutionary prospects of the existence of this junk RNA along with the integrated networks involving chromatin remodelling, dosage compensation, genome imprinting, splicing regulation, post-translational regulation and proteomics. In conclusion, all the major human diseases are discussed with a facilitated technology transfer, advancements, loopholes, and tentative future research prospects have also been proposed.